2013
DOI: 10.7860/jcdr/2013/5416.3127
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Telmisartan on the Regression of the Left Ventricular Hypertrophy in the Patients of Essential Hypertension

Abstract: Introduction: An increase in the Left Ventricular Mass as a result of muscle hypertrophy, has emerged as a powerful pressure independent risk factor for the cardiovascular mortality and morbidity. It is associated with a risk of death that is 3 times greater than the risk which is associated with hypertension alone. For the development of Left Ventricular Hypertrophy (LVH), in addition to a chronic increase in the pressure and/or volume overload, an elevation in the plasma ACE activity, plasma aldosterone leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…First, VCP attenuated the cardiac response to pressure overload by inhibiting the mechanical stretch‐induced reprogramming of fetal genes, which is a known mechanism of LVH. Secondly, it has been reported that AngII plays an important role in pathological cardiac hypertrophy beyond blood pressure elevation (Misra et al ., ). Our data showed that VCP was downregulated in AngII‐induced hypertrophic cardiomyocytes in a dose‐ and time‐dependent manner, whereas the overexpression of VCP prevented these AngII‐induced changes.…”
Section: Discussionmentioning
confidence: 97%
“…First, VCP attenuated the cardiac response to pressure overload by inhibiting the mechanical stretch‐induced reprogramming of fetal genes, which is a known mechanism of LVH. Secondly, it has been reported that AngII plays an important role in pathological cardiac hypertrophy beyond blood pressure elevation (Misra et al ., ). Our data showed that VCP was downregulated in AngII‐induced hypertrophic cardiomyocytes in a dose‐ and time‐dependent manner, whereas the overexpression of VCP prevented these AngII‐induced changes.…”
Section: Discussionmentioning
confidence: 97%
“…Telmisartan can also reverse myocardial remodeling and improve LVH in hypertension. 1719 Moreover, our previous results suggested that telmisartan could reduce perirenal adipose tissue-derived leptin paracrine activity and exert an indirect renoprotective effect on MetS rats by restoring the balance between angiotensin II-AT1R and angiotensin-converting enzyme 2-angiotensin (1–7)-Mas axes. 20 The present study therefore investigated whether telmisartan can reverse myocardial remodeling by reducing leptin autocrine activity induced by local Ang II in rats with hypertensive LVH, and assessed the potential molecular mechanisms underlying the effects of telmisartan on hypertensive LVH.…”
Section: Introductionmentioning
confidence: 99%